An Unexpected Circumstance: Acute Dystonic Reaction in the Setting of Clozapine Administration. (February 2019) - Kaplan, Alexander Morris; Pitts, William Bradly; Ahmed, Iqbal
Clozapine is a second-generation antipsychotic typically reserved for refractory psychotic disorders due to its high-risk side effect profile to include agranulocytosis, with its attendant need for regular blood draws. While reports of extrapyramidal symptoms (EPS), including acute dystonic reactions, are exceedingly rare, we present the case of a 44-year-old male with a long-standing history of treatment-resistant schizoaffective disorder and no history of EPS who experienced an acute buccal dystonic reaction in the setting of clozapine initiation and discontinuation of depot and oral risperidone. This case report presents one of the few documented episodes of acute dystonic reactions occurring in the setting of clozapine administration. Based upon the patient's history and the dosing time line of the medications, we propose that an interaction between the clozapine and residual risperidone was responsible for the development of the acute buccal dystonia.